"It'll make my brother's education better than mine. We need that.": Youth of Color Activating Their Community Cultural Wealth for Transformative Change. Issue 3 (3rd July 2022) - Salisbury, Jason
ABSTRACT: This research presents a counterstory to traditional views of leadership by demonstrating how two groups of youth of color were able to draw on their community cultural wealth to engage in transformative school and district improvement. Findings illuminate the ways that youth were able to draw on the familial, navigational, resistant, social, aspirational, and linguistic capitals of their communities to revision leadership toward transformative ends. My discussion demonstrates how youth of color were able to identity different causes of inequity, work from the margins, and shift the locus of power to offer new insights into equitable school leadership.